Exploring Two Decades of Indigenous Knowledge Integration in Science Education: A Bibliometric and Systematic Literature Review - Nurfaizah, Dwi Ayu; Sarawati, Tia; Aminatun, Tien (Proceeding International Conference on Religion, Science and Education, 2025)
Indigenous Knowledge (IK) is an important factor in scientific knowledge in education globally. However, IK research is treated as a type of unfounded knowledge that is considered not to provide scientific solutions. As a result, the purpose of this research is to provide insight into IK research and IK integration patterns in science education over the last two decades from 2004 to 2024. The articles consist of 274 articles from the Scopus databases. This study uses a combination of bibliometric analysis and the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) protocol to provide a comprehensive view of IK research in science education. Bibliometric data was collected using VOSviewer and Biblioshiny software to provide visualization of publication analysis, information, author collaboration, to understand geographical distribution, as well as research topic trends related to the integration of indigenous knowledge. A systematic literature review is conducted to explore the researches in the selected articles systematically in contributing to the understanding of culture-based science concepts and their relevance in scientific knowledge. The findings show a significant increase in publications related to this topic. In addition, the study also highlights the challenges of incorporating local cultural perspectives into formal science curricula and suggests policies that can support the further development of the integration of indigenous knowledge in science education. The results of the research provide valuable insights for future research trends; The results of the study further highlight opportunities to build research partnerships to strengthen policy making and implementation.